DNA Identification of Biological Traces in Forensic Casework for Investigation of Illegal Hunting in Belarus - I. S. Tsybovsky; S. A. Kotova; T. V. Zabavskaya; E. A. Spivak; O. N. Lukashkova (Теория и практика судебной экспертизы, 2018)
The article discusses molecular genetic identification of biological traces of wild animals used in forensic casework of illegal hunting of representatives of the order Artiodactyla – moose, red deer, roe deer, wild boar, and European bison. The question of species identification as an essential stage for correctindividual identification is discussed taking into account previous scientific and forensic studies. The paper also describes the modern method of species identification consisting of cross-species locus amplification, as well as primer cross-species transfer application in forensic research. Additionally examples of wild boar vs. domestic pig and European bison vs. cattle samples differentiation as well as results of the study of genetic diversity in the European wild boar population are given.